A Mechanochemical‐Assisted Oxidation of Amines to Carbonyl Compounds and Nitriles. Issue 37 (1st August 2017) - Gaspa, Silvia; Porcheddu, Andrea; Valentoni, Antonio; Garroni, Sebastiano; Enzo, Stefano; De Luca, Lidia
Abstract : A mild, efficient, metal‐ and solvent‐free oxidation of primary amines to aldehydes, ketones, and nitriles under ball‐milling conditions is presented. This method has proved to be compatible with various functional groups and only requires easily accessible starting materials. Simple purification of the reaction mixtures by short‐column chromatography afforded pure aldehydes, ketones, and nitriles as products. Abstract : A mild, efficient, metal‐ and solvent‐free oxidation of primary amines to aldehydes, ketones, and nitriles under ball‐milling conditions is presented. This method has proved to be compatible with various functional groups and only requires easily accessible starting materials. Simple filtration of the reaction mixture through pads of silica gel affords pure aldehydes, ketones, and nitriles as products.